Exploring a system architecture of content-based publish/subscribe system for efficient on-the-fly data dissemination - Yoon, Daegun; Park, Gyudong; Oh, Sangyoon (Concurrency and Computation: Practice and Experience, 2021)
In a cloud-scale publish/subscribe messaging system, it is difficult to partition subscription data among several servers. Without a sophisticated scheme and a system architecture, the messaging system would either waste resources or fail to deliver messages on time. In this study, we propose DRDA, a dynamic replication degree adjustment technology, for efficient message delivery. The technology calculates and maintains the number of subscription replications at a reasonable level by monitoring the statuses of servers, based on the number of subscription replications and the frequency of event dissemination. To verify the effectiveness of our proposed scheme and system architecture, we build a prototype of a content-based publish/subscribe system that dynamically adjusts the number of replications among brokers. Furthermore, we compare the load balance, resource overhead, and performance of a publish/subscribe system with DRDA with a publish/subscribe system without DRDA. The experimental results show that DRDA outperforms other approaches under various parameter configurations. We have added the prototype code to a GitHub repository to make it publicly available.
Keywords: Content-based publish/subscribe systems; Data dissemination; Dynamic replication; Event dissemination; Message delivery; Publish/subscribe messaging; Publish/Subscribe system; System architectures; load balancing; publish/subscribe system; space partitioning; subscription replication